Identification and evaluation of enzymes gelatinase, amylase, and catalase produced by rice root endophytic bacteria isolated from Hai Duong with antimicrobial properties against \(Xanthomonas oryzea\) pv. Oryzea - Phuong, Nguyen Van; Linh, Nguyen Thuy; Duy, Trinh Dinh; Khanh, Tran Le Nam; Giang, Do Doan Thu; Linh, Ta Thi Thuy; Nga, Mai Thi Phuong; Huong, To Thi Mai; Chung, Mai Duc; Ha, Chu Hoang; Binh, Le Tran (Academia Journal of Biology, 2021)
Endophytic bacteria (EB) possess different beneficial traits. Endophytic microbes are often functional in that they may carry nutrients from the soil into plants, modulate plant development, increase stress tolerance of plants, suppress virulence in pathogens, increase disease resistance in plants, and suppress development of competitor plant species. They may enhance plant development by carrying nutrients from the soil into plants and protect plants against phytopathogens by synthesizing extra-/intracellular proteolytic enzymes, as well as releasing antimicrobial metabolites and competing with pathogens for habitation and nutrients. In this study, we investigated the ability to produce exo/endo-enzymes such as gelatinase, amylase, and catalase, and antagonistic activity of 77 EB strains isolated from lowland rice roots grown in Doan Ket commune, Thanh Mien district, Hai Duong province, Vietnam. Out of 77 isolates, 76 (98.71%) showed the ability to liquefy gelatin after 7 days with different rates of hydrolysis. The test of starch hydrolysis revealed 58 (75.33%) isolates that were able to hydrolyze starch. Fifty-one out of 77 isolates (66.24%) were able to produce catalase. The antagonistic activity of rice root endophytic bacteria was determined against bacterial leaf blight disease-causing pathogen Xanthomonas oryzae pv. oryzae (Xoo), strains X19.2 and VX41. We found that three isolates (TP5, TP7, TP11) showed the ability to inhibit the growth of strain VX41 and twelve isolates (TP3, TP7, TP8, TP9, TP10, TP11, TP12, TP13, TP15, TP17, TP21, TP23) were able to inhibit the growth of strain X19.2. These results are served as a venue for further investigation in planta under the conditions of net house and field trials in order to confirm the potential strains for the development of bioinoculant toward controlling the disease caused by Xoo.